A Pilot Study of Responses to Suctioning Among Neonates on Bubble Nasal Continuous Positive Airway Pressure. (December 2017) - Sweet, Michele; Armbruster, Debra; Bainbridge, Erin; Reiner, Brianna; Tan, Alai; Chipps, Esther
Abstract : Background: Maintenance of a patent airway while the neonate is on nasal continuous positive airway pressure (nasal CPAP) requires vigilant monitoring and oral/nasopharyngeal suctioning. Currently, no evidence-based guidelines for safe suctioning in neonates while on bubble nasal CPAP have been published. Purpose: (1) To characterize the clinical and behavioral responses of neonates on bubble nasal CPAP in a level III neonatal intensive care unit following routine oral and nasopharyngeal suctioning. Methods: This pilot study has a 1-sample within-subject repeated-measures design in which neonates (N = 16) served as their own control. Data on a neonate's physiological and behavior measures (heart rate, respiratory rate, oxygen saturation [SaO2 ], and Premature Infant Pain Profile [PIPP] score) were collected before, during, and after the completion of suctioning sequence. Finding/Results: A total of 16 neonates with a mean gestational age of 29.76 weeks and an average day of life of 3.4 were enrolled. The infant's heart rates did not differ significantly ( P = .51) across the suctioning sequence. There were no statistical significant changes in the average respiratory rate across the suctioning sequences ( P = .79). SaO2 demonstrated a drop between baseline and after each suctioning ( P < .001). The PIPP score demonstrated a precipitous increase throughout the procedure ( P < .001). On average, it took 9.5 seconds (SD = 4.9) to complete the suctioning sequences. Implications for Practice: Our results suggest that the guideline tested is safe and tolerated by infants. Implications for Research: This guideline should be tested in a larger sample and with neonates on other nasal CPAP systems.